KONTRIBUSI MODAL MANUSIA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI PAPUA DAN PAPUA BARAT - siti munawaroh; Tri Haryanto (Media Ekonomi, 2020)
The purpose of this study is to determine the contribution of human capital to economic growth in the provinces of Papua and West Papua. This study used Panel regression with the random effect models with the stata 13. The data used in this research are GDRP, mean years school, life expectancy, labor and capital expenditure from 40 districts / cities from 2011 to 2018. Overall human capital variables (average school year and life expectancy), capital expenditure has a positive and significant contribution to gross regional domestic product in the provinces of Papua and West Papua. Although, education health contribution (average school year is relatively greater than health (life expectancy).